2007
DOI: 10.1007/s10661-007-9867-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinity evolution and its relationship with dynamics of groundwater in the oasis of inland river basins: case study from the Fubei region of Xinjiang Province, China

Abstract: Soil salinization is an important worldwide environmental problem, especially in arid and semi-arid regions. Knowledge of its temporal and spatial variability is crucial for the management of oasis agriculture. The study area has experienced dramatic change in the shallow groundwater table and soil salinization during the 20th century, especially in the past two decades. Classical statistics, geostatistics and geographic information system (GIS) were applied to estimate the spatial variability of the soil salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 32 publications
(30 reference statements)
2
71
0
1
Order By: Relevance
“…Salt salinity is a common problem around the world, especially in arid and semi-arid areas (Wichelns and Qadir, 2014;Singh et al, 2013;Wang et al, 2008;Li et al, 2015) with low rainfall and high evaporation. Apart from the natural factors resulting in soil salinization, long-term irrigated agriculture with poor drainage system contributes to secondary salinization (Ouni et al, 2013;Qadir and Oster, 2004;Kitamura et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Salt salinity is a common problem around the world, especially in arid and semi-arid areas (Wichelns and Qadir, 2014;Singh et al, 2013;Wang et al, 2008;Li et al, 2015) with low rainfall and high evaporation. Apart from the natural factors resulting in soil salinization, long-term irrigated agriculture with poor drainage system contributes to secondary salinization (Ouni et al, 2013;Qadir and Oster, 2004;Kitamura et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mismanagement of water and fertilizer application can result in salt buildup in the soil-groundwater systems and deterioration of soil quality (Darwish et al, 2005). Wang et al (2008) investigated the Fubei region of Xinjiang and found that the area of soil salt accumulation was greater in irrigated than non-irrigated landscape types. Specifically, they found that soil salt had increased by 40.04% from 1983 to 2005 in cropland at about 0.43 t ha −1 year −1 , and that it occurred concurrently with an increase in the groundwater table of 1 m. Han et al (2011) investigated Karamay in Xinjiang and found that the mean rise in the groundwater table from September 1997 to October 2009 was 6.9 m and the infiltration of irrigation water accounted for over 90% of the total recharge of the groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…In these regions, water sources are frequently brackish and high-quality water for agricultural purposes is increasingly scarce due to rising demands from urban areas (Wang et al 2008). As a result, the proportion of crop production under deficit irrigation with poorer quality water is increasing.…”
Section: Introductionmentioning
confidence: 99%